Efeito da textura metalúrgica na resistência a abrasão de aços ao manganês - Damião, Carlos Alberto (2018)
The cost due to abrasive wear on ore extraction and processing is up to 15% of the maintenance cost. The cost reduction is strongly linked to the correct choice of material, abrasive wear resistant, for process plant and equipment. This work aims to verify the impact of metallurgical texture on the abrasion resistance of hot rolled Mn steels. This work was developed from a sample of field-worn steel from a worn sheet of a front and loader machine bucket used in a gold mine. A methodology that replicates, in the laboratory, the wear and tear observed in the field was developed, by tests of abrasive wear type rubber wheel.. This methodology was applied in samples of hot rolled biphasic hypoeutectoid Mn steels and with similar chemical compositions. Some of these steels have metallurgical texture, in the form of alternating bands, of ferrite and perlite, known as "banding" disposed in the rolling direction. Linear sclerometry tests were also performed on the samples. Samples were tested on the upper and lateral surfaces with reference to the rolling direction. It was evidenced that there was greater hardness in samples of steel without metallurgical texture and that there was anisotropy in the hardness of samples with metallurgical texture. A decrease in the wear rate was observed, when the abrasive tests changed from the upper surface to the lateral surface, it was 29 to 33% in samples without texture and from 37 to 40% in samples with metallurgical texture. The wear mark showed predominance of grooving of abrasive particles. The wear rates showed a linear correlation with the hardness and the energy expended to scratch the surfaces. The steels without metallurgical texture are more difficult to scratch. The analysis of the specific energy and wear rate parameters showed that exist anisotropy in samples with metallurgical texture presence. Among the materials tested, the use of manganese steels with metallurgical texture is not recommended for severe abrasion applications.